2011
DOI: 10.5005/jp-journals-10021-1021
|View full text |Cite
|
Sign up to set email alerts
|

A Computer-assisted Angular Photogrammetric Analysis of the Soft Tissue Facial Profile of North Indian Adults

Abstract: Introduction:The success behind orthodontic diagnosis and treatment planning lies in appropriate evaluation of the patient's soft tissue profile appearance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 19 publications
5
15
3
Order By: Relevance
“…The nasofrontal angle (G-N-Prn) showed significant sex differences in the adult Garo and the angle was wider in females. This is in agreement to the findings by Reddy et al (2011) in the North Indian population (136.71˚ ± 3.64˚ in males and 144.33˚ ± 1.75˚ in females), Fernandez-Riveiro et al (2003) for Spanish (138.57˚ ± 6.81˚ in males and 141.98˚ ± 6.06˚ in females), Anic-Milosevic et al (2008) for Croatian (136.38˚ ± 6.71˚ in males and 139.11˚ ± 6.35˚ in females) and Wamalwa et al (2011) for Kenyans (132.44˚ ± 6.91˚ in males and 137.97˚ ± 5.21˚ in females). However, Malkoc et al (2009) found no sex differences in this angle (146.03˚ ± 8.19˚ in males and 148.61˚ ± 6.66˚ in females).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…The nasofrontal angle (G-N-Prn) showed significant sex differences in the adult Garo and the angle was wider in females. This is in agreement to the findings by Reddy et al (2011) in the North Indian population (136.71˚ ± 3.64˚ in males and 144.33˚ ± 1.75˚ in females), Fernandez-Riveiro et al (2003) for Spanish (138.57˚ ± 6.81˚ in males and 141.98˚ ± 6.06˚ in females), Anic-Milosevic et al (2008) for Croatian (136.38˚ ± 6.71˚ in males and 139.11˚ ± 6.35˚ in females) and Wamalwa et al (2011) for Kenyans (132.44˚ ± 6.91˚ in males and 137.97˚ ± 5.21˚ in females). However, Malkoc et al (2009) found no sex differences in this angle (146.03˚ ± 8.19˚ in males and 148.61˚ ± 6.66˚ in females).…”
Section: Discussionsupporting
confidence: 94%
“…The mean value of nasofacial angle (G-Pg/N-Prn) found in the adult Garo population (40.27˚ ± 4.54˚ in males and 38.67˚ ± 4.05˚ in females) is more in comparison to the values given by Reddy et al (2011) (34.38˚ ± 1.77˚ in males and 33.69˚ ± 1.37˚ in females) but larger than Anicy-Milosivecy et al (2008) (29.53˚ ± 2.51˚ in males and 30.36˚ ± 2.38˚ in females). No significant sexual dimorphism was observed.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Ioi et al [23] stated that Japanese facial profile was highly convex for both males and females as both genders have a tendency of retruded lip position. Reddy et al [24] after calculating the total angular facial profile (G-Prn-Pg), it was found that the population of northern India has a nose more aquiline causing the facial profile to be more straight compared to the Europeans, and by calculating the angle G-Sn-Pg, the facial profile of the female population of north India were more convex than men. Anibor and Okumagba [25] stated that the higher values shown by the Urhobo females in their Nasomental and Mentocervical values and the lesser values in the Nasofrontal and Nasofacial angles compared to males imply that the females have a more protruded nose, less prominent glabella and bigger chin on their faces compared to males.…”
Section: Advances In Health Science Research Volumementioning
confidence: 99%
“…to standardize the distance (100 cm) between it and the participants [16,17]. The images were saved to a computer and stored in JPEG format for processing and analysis.…”
Section: Facial Image Capturing Landmark Identification and Distancementioning
confidence: 99%